2007
DOI: 10.1139/s06-028
|View full text |Cite
|
Sign up to set email alerts
|

Determination of first order rate constants for wetlands treating livestock wastewater in cold climates

Abstract: Four years of performance data from a free-water surface constructed wetland receiving dairy wastewater in Nova Scotia was used to compute first order reaction rate constants (Ka) for several parameters including BOD5, TP, TKN, NH4+-N, FC, and TSS. Flow rates at the inlet and outlet of the 5 m wide × 20 m long wetland were continuously measured to assess how external hydrologic influences affected the water budget of the wetland and the system treatment performance. The Ka values were calculated using inlet an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 14 publications
3
33
0
1
Order By: Relevance
“…However, from the data presented in this review both SSF and SF wetlands have also been found effective during winter (Table 3). Two studies [23,39] examined the year-round performance of SF CWs in Atlantic Canada and found that even with the seasonal fluctuations, SF CWs performed well and were suitable water treatment options. Steps can be taken to further improve winter performance of CWs, such as allowing snow and dead vegetation to accumulate on the surface of the wetland to help insulate the system [2,49] and supplemental aeration can prevent freezing [49].…”
Section: Cold Climate Considerationsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, from the data presented in this review both SSF and SF wetlands have also been found effective during winter (Table 3). Two studies [23,39] examined the year-round performance of SF CWs in Atlantic Canada and found that even with the seasonal fluctuations, SF CWs performed well and were suitable water treatment options. Steps can be taken to further improve winter performance of CWs, such as allowing snow and dead vegetation to accumulate on the surface of the wetland to help insulate the system [2,49] and supplemental aeration can prevent freezing [49].…”
Section: Cold Climate Considerationsmentioning
confidence: 99%
“…Of the plug flow assumptions required for the use of this model [64], the most inaccurate is the assumption that inflow and outflow are equal [23]. External hydrologic factors (surface flow into or out of the CW, precipitation, and ET) play important roles in either concentrating [44,65] or diluting [21,23,24,66] wetland effluent, which can skew treatment efficiency calculations.…”
Section: Areal Rate Constantmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, ammonification and nitrification were limiting reactions for further N removal in pretreatment. This could be due to a lack of DO supply for biological degradation of organic matter and nitrification, especially in the winter (Figure 2) [12]. A nitrifying intermittent sand filter or subsurface flow wetland, like W3 in Kadlec et al, 1997, could be beneficial for increasing nitrification.…”
Section: Yearmentioning
confidence: 99%
“…Algunos ejemplos de aplicaciones se pueden ver en Di Toro et al (1971), Mesplé et al (1995), Martín et al (1998), Broekhuizen et al (2012). En este estudio, todas las constantes calculadas, excepto la referente a la materia orgánica, están significativamente correlacionadas con la CH aplicada al sistema (Tabla 6-117,Figura 6-124), de acuerdo con otros autores (Coveney et al, 2002;Braskerud et al, 2002a;Jamieson et al, 2007;Trang et al, 2010;Chen et al, 2015). Esto nos permite estimar valores de K para las CH más altas.…”
Section: Resumen Valores De C *unclassified